COMMODIFICATION OF TODAY’S WAYANG TOPENG PERFORMANCEIN MALANG - Wahyunigtyas, Tri (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
Wayang Topeng is a drama-shaped performance performed by dancers wearing masks who not only hide their faces but there are also more essential and symbolic purposes.Wayang topeng performances are always associated with rites as a medium of worshiping ancestral spirits. Nowadays,Wayang Topeng is undergoing a change, from a routine event to be a show for tourists held by one of the hotels in Malang city. The change, in the performance’ format from a stage show into a tourism packagingshow, made the Wayang Topeng to experience a shift in its valuesand original meanings. It is suspected that it has shifted the cultural value ?that were once a traditional culture to the direction of mass culture. This phenomenon is seen not only as an adjustment to the media format, but as a form of commodification. This research seeks to uncover forms, processes, ideologies, and powers related to the commodification of Wayang Topeng performance. This qualitative research uses interview data and observations which were analyzed using interpertation technique.The method used were the art phenomenology research with a study of critical discourse analysis. From the analysis of Wayang Topengperformance through interviews with several sources and combined with relevant literatures, the results show that: (1). Content commodification happened in the Wayang Topeng performance; (2). The ideology behind the process of commodification is capitalism. The power behind commodification is market power.